The cult of St. Martin in Late Antique and Early Medieval Dalmatia (5th -11th c.): archaeological and hagiographical evidence - Vedriš, Trpimir (2007)
The proposed paper aims at examining the cult of St. Martin of Tours in the territory of Salonitan Bishopric – covering both territory of Late Antique province of Dalmatia and Early Medieval Croatian principality with the cities of Byzantine theme of Dalmatia. The evidence from the neighbouring areas of Istria and Lower Pannonia will be also taken in the consideration as these regions, not only shared common Classical (and in the case of Istria also Byzantine) heritage, but were incorporated in the Carolingian empire along with the Dalmatian hinterland around 800. Besides reviewing the places of the cult (archaeological and hagiotopographical data), the textual corpus of evidence will be seeked in the earliest hagiographical and liturgical texts originating in the Dalmatian cities. Along with the proposed areas, the additional field of inquiry might also include the analysis of the Dalmatian urban hagionymy. The central aim of the presentation is to establish the (however fragmentary) chronological layers of the cult of st. Martin in the proposed geographical framework and to detect the directions of its dissemination.